PREDIKSI PENJUALAN MOTOR PADA PT. SAMEKARINDO INDAH CABANG HANDIL VIII - Elfreda Aplonia Lau, EKA WAHYUNI, Robin Jonathan, (EKONOMIA, 2015)
The success of a company is reflected by management's ability to optimally take advantage of opportunities that can generate sales and profits as expected. PT. Samekarindo Beautiful Branch Handil need to know the number of sales of motor suzuki for the next period by way of predicting the number of sales based on the data held onÂ prior periods. Sales forecasting needed by the company as a basis for a decision to plan the next steps in order to increase the quantity of sales.Problem formulation Is the level of sales is Suzuki PT Samekarindo Indah in 2016 - 2020 increased? The purpose of this study was to determine and analyze Prediction Suzuki Motor Sales PT. Samekarindo Beautiful Branch Handil VIII in 2016 and 2020. This study is expected to provide benefits for: 1) PT Samekarindo Indah as input to predict and plan for suzuki motorcycle sales in 2016 - 2020. 2) Khasana Science, as addition of a reference in the field of management marketing, especially on the sales forecast. 3) .Peneliti further as a reference in the field of study of the same in the future.Basic Marketing Management theory, theory and theory of sales forecasting. The hypotheses are: PT.Samekarindo Suzuki Motorcycle sales in the year 2016 - 2020 has increased. This study uses a linear trend equation equipment and methods used is the Least Square method.Â The analysis process using the original sale of components, which consists of the annual data of the last 5 years. Linear Equation Formula Trend line is: Y = a + bx.Based on the analysis and discussion of the data obtained during the study, through trend forecasting equation, then the writer can conclude the following: 1) Prediction Sales of two-wheel motor vehicle brand Suzuki Satria larger type than the type of motor Thunder, Shogun and Smash. 2) forecast sales in the year 2016-2020 Satria type motor in the position of the first rank, a motor vehicle sales rankings Suzuki type of Thunder ranked second in the position of the motor vehicle Suzuki Shogun kind sales rank third position. While the two-wheel motor vehicles for the brand Suzuki Smash types are at the fourth level 3) forecast sales for five years from 2016-2020 to the amount of sales of the Suzuki of four types of products sold in Handil VIII is based on the analysis, it can be determined Forecast sales The fourth kind of motor vehicle Suzuki could be improved in the future - the future.